Implementasi Sistem Kendali MPPT Panel Surya Berbasis Algoritma Incremental Conductance - Muldi Yuhendri; Gatot Santoso Putra (Jurnal Teknik Elektro Indonesia, 2020)
Solar power plant (PLTS) is a renewable energy power plant that is starting to develop in Indonesia as fossil energy is decreasing as the main energy source for electricity generation. This PLTS works by converting sunlight energy into electrical energy using solar panels. Increasing the efficiency of PLTS can be done by controlling the solar panels at their maximum power point. The maximum power point of the solar panels can be obtained by finding the maximum solar radiation or by controlling the output voltage of the solar panels at the maximum power point using a power converter. This research proposed a maximum power point of solar panels by regulate the output voltage using boost converter, which is also called the maximum power point tracking (MPPT). MPPT control system is proposed using an incremental conductance algorithm which is implemented using Arduino Mega 2560 programmed with Matlab simulink. MPPT control system is designed for four 50 WP solar panels connected in parallel. The experimental results show that the proposed MPPT control system with the incremental conductance algorithm is able to control the output power of the solar panels at the maximum point